2020
DOI: 10.3390/ijerph17238846
|View full text |Cite
|
Sign up to set email alerts
|

The Retail Food Environment: Time for a Change

Abstract: Food retailers, manufacturers, and distributors exert powerful influence on our food choices through decisions about stocking, pricing, marketing, and promotional practices [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ref. [10] observed that the relationship between food environments and choice behavior is a complex one, which may explain the relative lack of success in demonstrating a strong relationship between food environments and food choice behavior. Nevertheless, the idea that behavior is influenced by the immediate environment [11,12] continues to drive investigation into how food environments impact food choice behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [10] observed that the relationship between food environments and choice behavior is a complex one, which may explain the relative lack of success in demonstrating a strong relationship between food environments and food choice behavior. Nevertheless, the idea that behavior is influenced by the immediate environment [11,12] continues to drive investigation into how food environments impact food choice behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding consumers underlying concerns and purchasing desires is essential to drive consumer interest in upcycled foods, which will in turn propel a demand that food manufacturers and their supply chain partners will be keen to fulfil. Besides, researchers have recently called for a change in the food retail industry so that this industry could become a participant in the global efforts to make food consumption healthier and more sustainable [8]. Hence, at this early stage, it is necessary to examine how consumers feel about buying and consuming upcycled foods.…”
Section: Introductionmentioning
confidence: 99%